Comparison of two different dosages of esmolol in the prevention of hemodynamic response due to electroconvulsive therapy - (:unkn) unknown (KURE ILETISIM GRUBU A S, 2010)
Objective: Because of tachycardia and sudden hypertension due to sympathetic discharge during electroconvulsive therapy (ECT), negative effects on many systems particularly cerebrovascular and coronary problems could occur. Hence it is very important to keep patients in stable hemodynamic status. Drugs used during ECT, which is a brief procedure, must have short half lives and fast metabolism features, but also should not effect seizure duration. In our study we aimed to compare the effect of two different doses of beta adrenergic blocker esmolol, which has a short half life, in preventing hemodynamic response. Material and Methods: The study has been planned as total of 104 ECT sessions on 26 patients in ages between 18 and 65 years and at least four sessions of ECT planned for each patient in ASA 1-3 risk group. The patients were decided to be included in or excluded from the study based on measurements obtained during first ECT session. Electroencephalographs (EEG) and Electromyelography (EMG) electrodes were connected. Blood pressure cuff was placed above the right elbow and it was inflated up to the least pressure needed to stop radial artery pulse just before anesthesia induction. Immediately after anesthesia induction; 0.9% sodium chloride, 0.5 mg/kg esmolol, or 1 mg/kg esmolol were randomly adminestered. The anesthesia team recorded the measurements without knowing which drug was given. The measurements of placebo (0.9% sodium chloride) recipients were named (Beginning). The measurements of 0.5 mg/kg esmolol and 1 mg/kg esmolol recipients were respectively called (Measurement I) and (Measurement II). ECT was delivered with ECT Thymatron system 4 bipolar machine. In monitoring seizure activities both EEG and EMG recordings, and also contraction time in BP cuff connected extremity recorded by stopwatch, were used. The measurements were recorded before giving medication (basal) and after ECT on 1st, 5th, 10th and 15th minutes. Electrocardiograph (ECG), pulse oxymetry, and PETAS KMA 265 R were monitored. Also peripheral oxygen saturation (SpO2), systolic (SAB), diastolic (DAB), mean artery pressure (OAB) and heart rate (KH) values and post-ECT maximum heart rate were recorded. Results: In this study 60 ECT sessions conducted on 20 patients were included, 6 patients were excluded. The average age of patients were 31.75 +/- 3.71; average body weight and electric current power were 71.65 +/- 5.3kg and 19.0 +/- 6.19, respectively. SAB, DAB, OAR and KH basal measurements were not significantly different. The 1st and 5th minute measurements showed significant difference among all 3 groups. There were significant differences between Beginning and Measurment I and Beginnning and Measurement II at 10th minute recordings, but no significant difference between Measurements I and II. The 15th minute measurements demonstrated no significant difference among all 3 groups. When dual comparisons of maximum heart rate measurements were conducted, strongly significant decreases were found in Measurement I and II according to Beginning and in Measurement II according to Measurement I. The differences between seizure durations among all three groups were not statistically significant. Conclusions: Esmolol 1 mg/kg dose kept hemodynamic response more stable than esmolol 0.5 mg/kg dose during ECT. No side effects were observed at both doses and no effects on seizure duration were detected. Based on this study, to prevent hemodynamic response in the process of ECT, a treatment plan must be done and 1 mg/kg esmolol might be a good choice.
Keywords: Electroconvulsive therapy; esmolol hydrochloride; hemodynamic response; PERIOPERATIVE MYOCARDIAL-ISCHEMIA; NEUROENDOCRINE RESPONSE; PRETREATMENT REGIMENS; SEIZURE DURATION; ANESTHESIA; SURGERY; BOLUS; THIOPENTONE